Strengths and limitations of a musculoskeletal model for an analysis of simulated meat cutting tasks - Pontonnier, Charles; de Zee, Mark; Samani, Afshin; Dumont, Georges; Madeleine, Pascal (Applied ergonomics, 2014)
This study assessed the capacity of a musculoskeletal model to predict the relative muscle activation changes as a function of the workbench height and the movement direction during a simulated meat cutting task. Seven subjects performed a cutting task alternating two cutting directions for 20 s at four different workbench heights. Kinematics, electromyography (EMG), and cutting force data were collected and used to drive a musculoskeletal model of the shoulder girdle. The model predicted the muscle forces exerted during the task. Both the recorded and computed activation of the muscles was then compared by means of cross-correlation and by comparison of muscle activation trends with respect to the workstation parameters, i.e. cutting direction and workbench height. The results indicated that cutting movements involving arm flexion are preferable to movement requiring internal arm rotation and abduction. The optimal bench height for meat cutting tasks should be between 20 and 30 cm below the worker's elbow height. The present study underlines a beneficial use of musculoskeletal models for adjusting workstation parameters. •The cutting movements involving arm flexion are preferable in terms of biomechanical loads.•The optimal bench height for the meat cutting task should be 20–30 cm below elbow height.•Musculoskeletal models can help to minimize the risk of developing WMSD.